Sheepdog [videorecording (DVD)] - Grayhm, Steven, 1981-; Grayhm, Steven, 1981-; Dallas, Matt, 1982-; Curtis-Hall, Vondie; Cooper, Lilli; Fumusa, Dominic, 1969-; Madsen, Virginia, 1961- (Freestyle Digital Media, 2026)
A decorated veteran court ordered into treatment learns redemption comes through connection not escape.